Wide Band Frequency Characterization of High Permittivity Dielectrics (High-K) for RF MIM Capacitors Integrated in BEOL - Lacrevaz, T.; Flechet, B.; Farcy, A.; Torres, J.; Vo, T.T.; Bermond, C.; Cueto, O.; Defay, E.; Gros-Jean, M.; Blampey, B.; Angenieux, G.; Piquet, J.; et al. (Proceedings of the IEEE International Interconnect Technology Conference, 2006)
High permittivity insulators (high-k) are progressively introduced in high-speed integrated passives and devices in order to optimize circuit performances. However, high-k properties are expected to vary with frequency as relaxation and resonance mechanisms occur. It is necessary to analyze and evaluate high-k behaviour from DC to microwave frequency. Real permittivity (K or epsiv' r ) and losses (eepsiv" r ) extraction is required over a wide band of frequency to select the most suitable insulator. The proposed method enables the characterization of as deposited thin (down to 60 nm) planar dielectrics integrated below a copper coplanar wave-guide up to 40 GHz. Results of Ta 2 O 5 and STO insulators are presented in this paper